Evaluasi Pemenuhan Aspek Cara Distribusi Obat yang Baik (CDOB) pada Pedagang Besar Farmasi (PBF) dan PBF Cabang di Bawah Pengawasan Balai Besar POM di Bandung Periode Januari – Juli 2024 - Asyifa Mughnitiyas; Raden Bayu Indradi (STIKes Ibnu Sina Ajibarang, 2025)
Cara Distribusi Obat yang Baik (CDOB) is a way of distributing/distributing drugs and/or medicinal ingredients with the aim of ensuring quality along the distribution line according to the requirements and purposes of its use. In the drug distribution process, Badan Pengawas Obat dan Makanan (BPOM) will supervise the product and distribution channels. If PBF has applied the CDOB aspect well, the PBF will get a CDOB certificate which is a valid document and can be used as proof that the PBF has met the requirements to distribute pharmaceutical products. The research was conducted using a qualitative method that is descriptive, a method of data collection by straightening documents obtained from the Certification section of the Balai Besar POM (BBPOM) in Bandung. The results of the study showed that PBF and PBF branches under the supervision of BBPOM in Bandung in the period of January - July 2024 did not 100% meet the CDOB aspect, from 69 PBF there were 6 PBF (8.70%) that had met > 80% of the CDOB aspect, 39 PBF (56.5%) that had met 50 - 79% of the CDOB aspect, and there were 24 PBF (34.8%) that met < 50% of CDOB aspects, from the 12 aspects of CDOB aspects of Building and Equipment had the highest percentage which was 10% with a total of 66 PBF out of 69 PBF or around 95.65% PBF did not meet the standards of Building and Equipment aspects.